Quorum-Sensing Regulator OpaR Directly Represses Seven Protease Genes in Vibrio parahaemolyticus - Chang, San-Chi; Lee, Chia-Yin (Frontiers in Microbiology, 2020)
Proteases play a key role in a wide range of bacteria physiological events. Microbial proteases used in pharmaceutical industry and biomedical applications. Vibrios are known as proteases-producing bacteria. Proteases transform polypeptides into shorter chains for easier utilization. They also play virulence factors in pathogens. The mechanism by which protease genes are regulated in Vibrio parahaemolyticus, an emerging world-wide human pathogen, however, still remains unclear. Quorum sensing is the communication system of bacteria. OpaR is the major quorum sensing regulator in V. parahaemolyticus. Herein we found that OpaR is a direct regulator of seven protease genes, including metalloprotease and serine protease, which are involved in environmental survival and bacterial virulence. Quantitative reverse-transcriptase PCR and luxAB assays indicated that OpaR repressed the seven protease genes. Furthermore, electrophoresis mobility shift assay proved that OpaR bound directly to the promoter region of seven protease gene. DNase I footprinting identify the sequence of these OpaR binding sites. ChIP-seq analyses revealed 435 and 835 OpaR-binding sites in the late-log and stationary phases, respectively. Among these OpaR-binding sequences showed a conserved OpaR-binding motif: ATCAATA. These results should further grow on our understanding of the protease regulation system in V. parahaemolyticus. ChIP-seq reports the OpaR motif within the V. parahaemolyticus genome for the first time and provides the database for OpaR direct regulon.